Fabellar prevalence, degeneration and association with knee osteoarthritis in the Chinese population - Hou, Weikun; Xu, Lin; Wang, Jingbo; Wang, Bo; Liu, Lin; Xu, Ke; Cai, Yuanzhen; Guo, Hao; Xu, Peng (Scientific reports, 2019)
The fabella is a sesamoid bone of the knee that can degenerate in some patients with osteoarthritis. The purpose of this study was to examine the prevalence and degeneration grades of fabellae in the Chinese population and to analyse their relationships with subject ages and knee osteoarthritis grades. The anteroposterior and lateral knee roentgenograms of 1150 subjects were recruited from the institutional database. The Kellgren-Lawrence scoring system was used to evaluate knee osteoarthritis. The degeneration grades of fabellae were scored in lateral roentgenograms by screening their shapes, sizes, subchondral sclerosis and osteophyte formation. The prevalence and degeneration of fabellae among ages, genders and knee sides were analysed by the Pearson Chi-Square test, and their relationships with knee osteoarthritis were analysed by the Spearman nonparametric correlation test. The overall prevalence of fabellae was 48.6% in 1359 knees. There was no significant difference in fabellar prevalence between the two sides ( χ ² = 0.025, P = 0.87437) and genders ( χ ² = 3.647, P = 0.05617), while the prevalence increased with the increasing ages of the subjects ( χ ² = 213.868, P < 0.001 ). The fabellar degeneration grades were correlated with age ( r = 0.5288, P < 0.001) and knee osteoarthritis scores ( r = 0.6892, P < 0.001 ). These results suggested that the fabellar prevalence and degeneration grades were correlated with age and knee osteoarthritis scores.